(cosec^2theta-1)tan^2theta=
Answers
Answered by
2
Answer:
hope it helps!
Step-by-step explanation:
mark me as brainliest and vote too please
Attachments:
![](https://hi-static.z-dn.net/files/d87/66687ae34162978b487305633ed2be24.jpg)
Answered by
0
Step-by-step explanation:
(cosec^2 theta -1) tan^2 theta
= take cosec^2 theta as 1÷sin^2 theta and take tan^2 theta as sin^2 theta ÷cos^2theta
=( 1÷sin^2theta-1)(sin^2theta ÷cos^2theta)
= (1-sin^2theta÷sin^2theta)(sin^2theta÷cos^2theta)
( 1-sin^2theta= cos^2theta)
= (cos^2theta÷sin^2theta)(sin^2theta÷cos^2theta)
it will get cancelled and becomes one
Then the answer is one
I hope this will help you
Similar questions
English,
5 months ago
Social Sciences,
5 months ago
Computer Science,
11 months ago
English,
11 months ago
Chemistry,
1 year ago
Hindi,
1 year ago